Spectroscopic Investigations and DFT Calculations on 3-(Diacetylamino)-2-ethyl-3H-quinazolin-4-one - Yusuf Sert; Fatih Ucun; Gamal A. El-Hiti; Keith Smith; Amany S. Hegazy (Journal of Spectroscopy)
The theoretical and experimental vibrational frequencies of 3-(diacetylamino)-2-ethyl-3H-quinazolin-4-one (2) were investigated. The experimental Laser-Raman spectrum (4000–100 cm−1) and FT-IR spectrum (4000–400 cm−1) of the newly synthesized compound were recorded in the solid phase. Both the theoretical vibrational frequencies and the optimized geometric parameters such as bond lengths and bond angles have for the first time been calculated using density functional theory (DFT/B3LYP and DFT/M06-2X) quantum chemical methods with the 6-311++G(d,p) basis set using Gaussian 03 software. The vibrational frequencies were assigned with the help of potential energy distribution (PED) analysis using VEDA 4 software. The calculated vibrational frequencies and the optimized geometric parameters were found to be in good agreement with the corresponding reported experimental data. Also, the energies of the lowest unoccupied molecular orbital (LUMO), highest occupied molecular orbital (HOMO), and other related molecular energies for 3-(diacetylamino)-2-ethyl-3H-quinazolin-4-one (2) have been investigated using the same computational methods.